Adverse outcomes of proton pump inhibitors in patients with chronic kidney disease: The CKD‐REIN cohort study. Issue 7 (19th January 2021) - Liabeuf, Sophie; Lambert, Oriane; Metzger, Marie; Hamroun, Aghiles; Laville, Maurice; Laville, Solène M.; Frimat, Luc; Pecoits‐Filho, Roberto; Fouque, Denis; Massy, Ziad A.; Jacquelinet, Christian; Stengel, Bénédicte; et al.
Abstract : Aims: Long‐term use of proton pump inhibitors (PPIs) has been associated with adverse kidney events in the general population, but their impact among chronic kidney disease (CKD) patients is unclear. We studied the prevalence and incidence (new users) of PPI prescriptions and their relation to kidney outcomes and mortality in CKD patients. Methods: We collected drug prescriptions prospectively in a cohort of 3023 nephrology outpatients with CKD stages 2–5 at inclusion. Hazard ratios (HR, 95% confidence intervals [95% CI]) for acute kidney injury (AKI), end‐stage kidney disease (ESKD), and mortality associated with new PPI prescriptions as a time‐dependent variable were estimated with cause‐specific Cox models in 1940 non‐users with eGFR ≥ 15 mL/min/1.73 m 2 at baseline, adjusted for comorbidities, laboratory data and drugs. Results: There were 981/3023 (32%) prevalent users (67 ± 13 years, 65% men) at baseline, and 366/3023 (12%) were prescribed PPI (new users) over a median follow‐up of 3.9 years (interquartile range, 3–4.2). Among these new users, their median cumulative duration of prescription was 1 year (interquartile range: 0.4–2.3). During follow‐up, 354 patients developed ESKD and 216 died before ESKD. The adjusted HRs associated with PPI prescription were 1.74 (95% CI, 1.26–2.40) for ESKD and 2.42 (95% CI, 1.73–3.39) for all‐cause mortality. Over the first 3 years of follow‐up, 211 AKI events had occurred. The adjusted HR for AKI associated with PPI prescription was 2.89 (95% CI, 1.91–4.38). Conclusions: Long‐term PPI prescription was common in CKD patients. Our results call attention to its potential risks of both acute and chronic kidney failure.